PENYELENGGARAAN MAKAN KELUARGA DI KAMPUNG NAGA KABUPATEN TASIKMALAYA - Sobariyah, Saribanon; Ai Nurhayati; Muktiarni (LPPM Universitas Negeri Jakarta, 2024)
Abstract The uniqueness of the community in Naga Village is a form of a nature conservation area that has the privilege of preserving culture. However, at this time modernization can affect people's habits, therefore researchers need to document how family meals are organized in Naga Village. The purpose of this study is to find out and obtain an overview and information on how to organize family meals in Naga Village. This research is qualitative research with a descriptive method. The participants in this study are 3 families living in Naga Village. Data collection techniques use interviews, observations, and documentation. The results of the study showed that the meal time that was carried out followed the meal time in general, namely breakfast, lunch, and dinner and there were interruptions. The habit of eating is to gather together and eat in the kitchen in a lesehan position. The staple food is white rice and the daily meal menu is adjusted to the availability of foodstuffs. There is a celebration menu made at the time of the Hajat Sasih, namely “nasi tumpeng”. The source of materials obtained is to buy and use crops, the heat source used is a furnace with wood fuel. The way food is served using the appropriate tools for the dish and then served in the kitchen and eaten together. The recommendation of this study is aimed at the next researcher, namely to conduct further research on the menu of the celebration of wishes in the form of tumpeng rice. Keywords: Keywords: Family Meal Implementation, Lesehan, Naga Village